2018
DOI: 10.1016/j.pacfin.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Stock liquidity, corporate governance and leverage: New panel evidence

Abstract: We examine the effect of stock liquidity and corporate governance on the firm's leverage decision in the order-driven stock trading system and less stringent governance environment of Australia. Using a sample of 1,207 non-financial firms from 2001 to 2013, resulting in 9,855 firm-year observations, we find the posited negative stock liquidity-leverage relation, confirming prior research observations that firms with more liquid stocks are significantly less leveraged. We also find a significant and negative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 76 publications
4
39
0
2
Order By: Relevance
“…This research used proxy beta as the systematic risks, while some previous researches used proxy beta as its measurement (Ahmad & Qais, 2017; Akbari & Mohammadi, 2013; Bhatti et al, 2010;Dunn, 2001). Meanwhile, the independent variables, leverage used debt to total assets (Nadarajah et al, 2016). Then, size used total assets as the company size, and profitability used return on assets.…”
Section: Methodsmentioning
confidence: 99%
“…This research used proxy beta as the systematic risks, while some previous researches used proxy beta as its measurement (Ahmad & Qais, 2017; Akbari & Mohammadi, 2013; Bhatti et al, 2010;Dunn, 2001). Meanwhile, the independent variables, leverage used debt to total assets (Nadarajah et al, 2016). Then, size used total assets as the company size, and profitability used return on assets.…”
Section: Methodsmentioning
confidence: 99%
“…The independent variable for the study were leverage (LEVE) which is measured by total liabilities divided by total assets, income level (INCM) is measured as total revenue divided by total assets, debt ratio (DEBTR) is measured as total debts (short and long) divided by total assets consistent with Baños-Caballero, Garcí a-Teruel and Martí nez-Solano (2014), Sivathaasan et al (2016), Al-najjar and Clark (2017). Internationalization which is a dummy variable is measured as '1' for firms involve in international activities like export and import of product, '0' for otherwise consistent with the study of Angulo-ruiz et al (2018), dividend payout (DIVPO) was measured as '1' for firms which have paid dividend within the study period '0' for otherwise following the research of Gill and Biger (2013).…”
Section: Independent Variablementioning
confidence: 99%
“…In this quest, some studies examine the relationship between corporate governance and some financial indicators. They found that there is a significant and negative relationship between corporate governance and leverage; (Nadarajah et al, 2016), negative relationship between board size and cash holding; (Al-najjar & Clark 2017), the FR categories of solvency and profitability and the CGI categories of board structure and ownership structure are the most important features in bankruptcy prediction; , and better governed firms reduce the profitability of insider sale; (Dai et al, 2016). Contradictory, (Ramli & Ramli 2016) found that all board attributes fail to prove their significant influence on the profit moderation as well as profit maximization.…”
Section: Literature Reviewmentioning
confidence: 99%